Functional and physicochemical properties, and storage stability of instantized purple sweet potato (Ipomoea batatas L.) Powder - Nevara, Gita Addelia (2015)
Purple-flesh sweet potatoes (Ipomoea batatas L.) are commonly consumed as boiled tuber, traditional cakes and crispy snacks. Developing instantized purple sweet potato powder (IPSPP) from this tuber serves as a vehicle for adding value to this local commodity. Most of studies related to the production of powder from tubers focused only on the antioxidant and physical properties and not much research has been done on the resistant starch. Therefore, this study was carried out to evaluate the effects of processing methods and storage temperatures on the antioxidant, physical and resistant starch contents of IPSPP. IPSPP was produced using a double drum drier (set at 2 rpm and steam pressure of 3 bars). The first part of the research involved studying the effects of two preheating treatments which were boiling and steaming prior to drum drying on the antioxidant, physical and resistant starch properties of IPSPP. It was found that IPSPP pretreated by steaming process had significantly higher (p≤0.05) total anthocyanin (121.71 mg/100 g), moisture content (3.21% db), powder yield (243.02 g/kg) and resistant starch content (3.06 g/100 g) than boiling pretreatment. There was no significant difference (p>0.05) between boiling and steaming in terms of antioxidant capacity (101.35 to 101.75 µmol TE/g and 134.35 to 134.40 µmol TE/g for DPPH and FRAP, respectively), physical properties such as water activity (0.49 to 0.50), color values, water solubility index (21.76 to 25.54) and non resistant starch content (51.68 to 60.94 g/100 g). The results showed that steaming of raw tuber is recommended as preheating treatment prior to drum drying. In the second part of the research, an attempt was made to increase the resistant starch content of IPSPP by pretreatment of the steamed-mashed tuber with pullulanase enzyme. Effects of the enzyme concentration and hydrolysis time on the resistant starch and total anthocyanin contents were evaluated. The optimum hydrolysis conditions for production of the maximum amount of resistant starch and total anthocyanin contents at 60ºC were 0.5% v/w pullulanase at 8 h of incubation period. Hydrolysis of purple sweet potato (PSP) puree with pullulanase enzymes significantly (p≤0.05) increased the resistant starch content (5.44 g/100 g), but concurrently reduced the antioxidant capacity of the IPSPP (5.20 µmol TE/g). The latter effect could probably due to long period of incubation and additional heating process required for enzyme inactivation that destroyed the antioxidants in the IPSPP. The final part of the study focused on the storage stability of IPSPP at different storage temperatures. The total anthocyanin, DPPH radical scavenging activity, moisture and resistant starch contents of the samples were evaluated at every two month intervals for a duration of 12 months. The result showed that storage periods had significant effects (p≤0.05) on the total anthocyanin (185.32 and 197.61 mg/100 g at ambient and chilled storages, respectively), scavenging activity (74.16 and 77.48 µmol TE/g at ambient and chilled storages, respectively), moisture (6.35 and 8.10 % db at ambient and chilled storages, respectively) and resistant starch content (1.57 and 1.73 g/100 g at ambient and chilled storages, respectively) of IPSPP. The antioxidant, physical and resistant starch properties of IPSPP at 12 months of storage were compared with the control sample. The physicochemical properties of IPSPP changed remarkably after 12 months of storage at ambient (25±2ºC) condition. Sample stored at chilled storage (4±2ºC) had similar properties to the control sample. The most suitable storage temperature for IPSPP is at chilled condition (4±2ºC) because at this condition the antioxidant, physical and resistant starch properties product was stable for 12 months with significant increment in the total anthocyanin content. Based on these findings, it can be concluded that processing methods and storage conditions influence the antioxidant, physical and resistant starch contents of IPSPP.